'Rachel's not here': Constructed dialogue in gossip. (June 2015) - Mohammad, Abeer; Vásquez, Camilla
<x xml:space="preserve">Abstract</x> Sociolinguistic research has demonstrated that gossip is a co‐constructed phenomenon, which allows participants to establish solidarity and build alignments with each other, while evaluating an absent party. Gossip can also serve important social functions, such as helping to establish and reconfirm group norms and values. The present study provides a detailed analysis of an extended gossip episode that occurred within an institutional context: a study group interaction at a U.S. university. Our analysis shows how, in gossip, constructed dialogue both prompts and legitimizes pejorative evaluations towards an absent third party, and is actually the pivot around which group members negotiate values and norms in the process of arriving at a shared moral stance. Our analysis also demonstrates that alignment in gossip interactions is tenuous and must be continuously renewed.